THE ROLE OF THE BATAM STATE PROSECUTORIN PROSPECTING THE CASE OF FAKE VACCINE CERTIFICATES CASE STUDY CASE NUMBER: 541/PID.B/2021/PN BTM - Nick Kurniawan; Rahmi Ayunda (Universitas Internasional Batam, 2022)
At this time it is not uncommon for people to commit criminal acts, someone committing a criminal act must have certain reasons, for example economic factors accompanied by an element of compulsion. Of the various crimes that occur in society, one of them is the crime of counterfeiting, even today it is often found the crime of counterfeiting in various forms and developments that show the intellectual level of counterfeiting crimes that are increasingly complex. Here the author wants to make how the law enforcement process against criminal cases of falsification of letters, explain what the role of the prosecutor in enforcing the law against the criminal falsification of letters and what the author did during his internship in the batam state prosecutor's office. The author in working on this writing the author uses observation methods that are carried out systematically. In this case, the author visits the observation site to observe various things or conditions that exist at the scene. At the time of the internship in the batam state prosecutor's office, the author can learn how the prosecutors act in resolving the case reported by investigators until the trial process even until the case is broken.